BIMBINGAN KELOMPOK MELALUI TEKNIK PROBLEM SOLVING UNTUK MENINGKATKAN PENYESUAIAN DIRI SISWA TERISOLIR - Rosidah, Ainur (JURNAL FOKUS KONSELING, 2016)
Adaptation of isolated students is a kind of students incapacity in social relationshipsuch as be alone, and be avoided by milieu friends. This study aims to investigate theeffectiveness of group guidance by using problem solving technique toward isolatedstudents. This study used quantitative approach and quasi experimental method withnonequivalent pretest-posttest control group design. 26 students of seventh grade of StateIslamic Junior High School (Mts) Pringsewu were choosen as the sample. They wereselected by using simple random sampling technique. The research finding shows thatgroup guidance with problem solving technique is effective to improve adaptation ofisolated students.Keywords: group guidance, problem solving technique, and isolated students